Valuation of international oil companies : RoACE era - Petter Osmundsen; Frank Asche; Bård Misund; Klaus Mohn (Center for Economic Studies and ifo Institute (CESifo), 2005)
High oil prices are normally expected to stimulate exploration and the development of new oil and gas fields. But over the last few years, financial analysts have focused strongly on shortterm accounting return (RoACE) for benchmarking and valuation, and this has led to high capital discipline among oil and gas companies. We analyse how high oil prices can be explained in terms of an implicit capacity game between the oil companies, and explore the stability of the current equilibrium. Our approach is an investigation of a key assumption among financial analysts, namely the presumed positive relation between RoACE and stock market valuation. Based on panel data for 11 international oil and gas companies, we seek to establish econometric relations between market valuation on one hand, and simple financial and operational indicators on the other. Our findings do not support the perceived positive relation between reported RoACE and market-based multiples. Recent evidence also suggests that the stock market is increasingly concerned about reserve replacement and sustained profitable growth. The current high-price equilibrium is therefore hardly stable.
Keywords: M21; M41; 330; Mineralölwirtschaft; Unternehmenswert; Return on Investment; Börsenkurs; Betriebliche Kennzahl; Schätzung; Welt